(untitled) (Al-Qamar, 2025)
Water holds fundamental importance for the survival of human life and the growth of civilization. In the present era, the depletion of water resources and its reckless consumption have given rise to a severe global crisis. In this context, the Seerah of the Prophet ؑ provides us with a comprehensive and balanced guiding principle that not only nurtures spiritual training but also directs practical aspects of life. The Messenger of Allah ؑ emphasized moderation in the use of water and strictly forbade extravagance. Even during the act of ablution, a sacred ritual, he disliked wasting water and prohibited excessive use of it, even by the side of a flowing river. This teaching highlights the significance Islam places on the preservation of environmental resources.This paper will explore the preservation of water and the prohibition of its wastage in the light of the Prophet’s ؑ Seerah, particularly in the context of contemporary environmental challenges. It will make clear that if individuals and societies adopt the guidance of the Prophet ؑ, the water crisis can be controlled, and a sustainable and balanced way of life can be promoted. Thus, the Seerah of the Prophet ؑ is not only a source of spiritual reform but also a guarantee for the survival of human society and the environment. There is, therefore, a pressing need to present the prohibition of water wastage in the light of the Seerah to scholars and thinkers. It is to fulfill this very need that the present paper is being written.